2022
DOI: 10.3390/ma15155177
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Reduced Graphene Oxide–Al2O3 Nanofluid: Interaction among Testing Force, Rotational Speed and Nanoparticle Concentration

Abstract: The tribological properties of nanofluids are influenced by multiple factors, and the interrelationships among the factors are deserving of further attention. In this paper, response surface methodology (RSM) was used to study the tribological behavior of reduced graphene oxide–Al2O3 (rGO-Al2O3) nanofluid. The interaction effects of testing force, rotational speed and nanoparticle concentration on the friction coefficient (μ), wear rate (Wr) and surface roughness (Ra) of steel disks were investigated via the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This ionic liquid reduces both the running-in and the steady-state friction coefficient with respect to the base oils. The good tribological performance of MO is attributed to the formation of an easy shearing boundary layer, which also acts as an anti-wear and low-friction lubricant, reducing both friction and wear, particularly during the running-in period [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…This ionic liquid reduces both the running-in and the steady-state friction coefficient with respect to the base oils. The good tribological performance of MO is attributed to the formation of an easy shearing boundary layer, which also acts as an anti-wear and low-friction lubricant, reducing both friction and wear, particularly during the running-in period [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…diameter (D T ) and surface roughness of wear scar (Ra T ) for the 27 trials under different test conditions of were listed. However, the influence of multiple test parameters on the tribology behavior of lubricants is usually complex, especially for solid-liquid two-phase nanofluids [25]. The relationship between the various parameters describing the tribological performance is also intricate.…”
Section: Knn Machine Learningmentioning
confidence: 99%
“…To further examine the potential of utilising NPs for this purpose, Wu et al [ 19 ] investigated the tribological behaviour of the lubricant with TiO 2 NPs and found that using the nanolubricant can effectively alleviate the overflow and reduce the friction in the steel-to-steel sliding process. As a result, subsequent research has been dedicated to exploring the correlation between the performance of the nanolubricant and the specific characteristics of the added NPs [ 20 , 21 , 22 , 23 ]. Furthermore, other researchers [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] have incorporated TiO 2 , SiO 2 , CuS, Al 2 O 3 , and MoS 2 NPs into liquid lubricants for application in metal rolling.…”
Section: Introductionmentioning
confidence: 99%